2008
DOI: 10.1128/aem.01842-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dried Distillers’ Grain on Fecal Prevalence and Growth of Escherichia coli O157 in Batch Culture Fermentations from Cattle

Abstract: Distillers' grains (DG), a by-product of ethanol production, are fed to cattle. Associations between Escherichia coli O157 prevalence and feeding of DG were investigated in feedlot cattle (n ‫؍‬ 379) given one of three diets: steam-flaked corn (SFC) and 15% corn silage with 0 or 25% dried distillers' grains (DDG) or SFC with 5% corn silage and 25% DDG. Ten fecal samples were collected from each pen weekly for 12 weeks to isolate E. coli O157. Cattle fed 25% DDG with 5 or 15% silage had a higher (P ‫؍‬ 0.01) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 37 publications
3
43
1
Order By: Relevance
“…This study also showed that not only overall prevalence but also high-shedder prevalence was dependent on DG inclusion level. Previous studies documenting the relationship between E. coli O157:H7 prevalence and feeding DG differed in the inclusion level (10 to 50%) and form of DG (wet or dried) fed to cattle; further, the magnitude of the reported association has not been consistent (10,11,28). Although both dried and wet DG have been studied, the two have not been directly compared in terms of their impact on E. coli O157:H7 prevalence.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This study also showed that not only overall prevalence but also high-shedder prevalence was dependent on DG inclusion level. Previous studies documenting the relationship between E. coli O157:H7 prevalence and feeding DG differed in the inclusion level (10 to 50%) and form of DG (wet or dried) fed to cattle; further, the magnitude of the reported association has not been consistent (10,11,28). Although both dried and wet DG have been studied, the two have not been directly compared in terms of their impact on E. coli O157:H7 prevalence.…”
Section: Discussionmentioning
confidence: 93%
“…Distillers' grains for use in cattle diets are available in wet (WDG) or dry (DDG) form. The association between feeding DG and E. coli O157:H7 prevalence has been shown with both forms (10,28), but no study has directly compared the two forms. The levels of DG supplementation in cattle diets generally range from 10 to 50% (dry matter basis) depending on whether the coproduct is used as a protein or energy source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the initiation and the termination of the experiment, abalones in each aquarium were collectively weighed using an electric balance following a 24 h starvation period. tional value and low cost, and it is currently mainly being tested for use as a possible energy source in ruminant diet programs (Jacob et al, 2008). However, due to the enhanced availability and potential cost-benefit of DDG, incorporating DDG into aquafeed may present a large economic value.…”
Section: Experimental Animal and Feeding Experimentsmentioning
confidence: 99%
“…Both bacteria have been associated with numerous outbreaks in the United States (Ratnam et al, 1988;Nightingale et al, 2004;CDC, 2014). Cattle are reservoirs of E.coli O157:H7 as they are found in the lower gastrointestinal tract, specifically the mucosal surface of the rectum (Naylor et al, 2003;Gyles, 2007;Hussein, 2007) and also in feces (Callaway et al, 2003;Berg et al, 2004;Jacob et al, 2008aJacob et al, , 2008b. The detection of Listeria monocytogenes was also reported in the feces of ruminants, particularly cattle (Pell, 1997;Pauly et al, 1999).…”
Section: Introductionmentioning
confidence: 99%